PENILAIAN KEPUASAN PELAYANAN PENERBITAN PASPOR DI KANTOR IMIGRASI KELAS 1 PALEMBANG - Nyayu Ully Auliana (Program Magister Manajemen Indo Global Mandiri University, 2021)
This research examines the passage of the applicant passport service, the supporting and inhibiting factors that influence the passport passage. This research aims to determine the level of satisfaction of publishing service of passport in the Immigration Office Class 1 Palembang through assessment of realiblity, responsiveness, assurance, emphaty, tangible and internal factor. In this research using data collection methods through literature study books and immigration data, direct field observation, interviews with Kasi Lantaskim and the division of questionnaires to the applicant at Immigration Office Class 1 Palembang. Result of data using quantitative and qualitative analysis models. The results of this research that as many as 50% to 73% of the public are satisfied with the service received at the Immigration Office Class 1 Palembang, and as many as 27% to 50% of people still argue less satisfied due to some inhibiting factors such as network interference factor and the delay of officers in keeping the promise of service.